Evidence of Wave-Particle Duality for Single Fast Hydrogen Atoms - Schmidt, H. T.; Fischer, D.; Berenyi, Z.; Cocke, C. L.; Gudmundsson, M.; Haag, N.; Johansson, H. A. B.; Källberg, A.; Levin, S. B.; Reinhed, P.; Sassenberg, U.; Schuch, R.; et al. (My University, 2008)
We report the direct observation of interference effects in a Young’s double-slit experiment where the interfering waves are two spatially separated components of the de Broglie wave of single 1.3 MeV hydrogen atoms formed close to either target nucleus in H++H2 electron-transfer collisions. Quantum interference strongly influences the results even though the hydrogen atoms have a de Broglie wavelength, λdB, as small as 25 fm.